LUXURY GOODS VS NECESSITY GOODS: WHICH GOODS CONTRIBUTE TO ENHANCEMENT OF THE NATIONAL WEALTH? - Fujita, Yasunori (International Journal of Research -GRANTHAALAYAH, 2018)
How do luxury goods affect the national wealth? This is a topic that can go back to the seventeenth century. In the present paper, we tackle this problem by examining if the innovation accelerates the generation of luxury goods market. The framework we construct is a model where one firm intends an investment under uncertainty that is expressed by geometric Brownian motion. It is revealed that innovation accelerates the generation of luxury goods market, that is, luxury goods contribute to market generation, as well as enhancement of the national wealth.